Implementation of a dynamically flexible optoelectronics logic gate using a fiber laser, numerical study - Afanador Delgado, S.; Jaimes Reátegui, R.; Sevilla Escoboza, R.; Huerta Cuéllar, G.; García López, J.; López Mancilla, D.; Camacho Castillo, L.; Castañeda Hernández, C. (Acta Universitaria, 2013)
We implement an algorithm to reproduce the behavior of a dynamic logic gate which consists of three elements: a fiber laser in chaotic regime, a threshold controller and the output of the logic gate. The output signal of the fiber laser is sent to the logic gate input as to the threshold controller; threshold controller output signal is sent at the entrance of the logic gate and also fed back to the fiber laser which changes their dynamic behavior. The output of the logic gate consists of a difference amplifier; this compares the signals sent by the threshold controller and the fiber laser, resulting logic output that depend on an accessible parameter in threshold controller. We present the numerical results of the implementation of a dynamic logic gate using fiber laser, which demonstrates the ability to change the type of logic gate by modifying a parameter of threshold control.
Keywords: Array; Array; Array